OS DESAFIOS DA ESTRATÉGIA DE COMUNICAÇÃO NO SETOR NUCLEAR: O CASO CNEN - Zarur, Roberto Ramos (2013)
The objective of this dissertation is to analyze the challenges of managing communication in a sector that has influenced opinion formation by strong impacts: the nuclear power industry. This sector is permeated by great controversy. Most often, the image of nuclear energy is associated with experiences, disasters, state secrets, radioactive waste, nuclear weapons, the risk of diseases like cancer, among others. Therefore, communication in the energy sector to society requires an integrated communication that makes the media with useful information to the population. It is important that the nuclear power industry knows how to communicate, or make common information. It is necessary to have it clear, simple, direct and easy to understand. In short, society must have access to information of public interest to feel peaceful about the safety and actions of regulatory authorities. This work is a case study which has been developed as a communication of the National Commission of Nuclear Energy (CNEN). The intention is to suggest improvements to make the communication process more effective and efficient between all parties involved.